1986
DOI: 10.1152/jn.1986.56.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory responses in the frontal opercular cortex of the alert cynomolgus monkey

Abstract: SUMMARYAND CONCLUSIONS1. The responses of 165 single taste neurons in the anterior operculum of the alert cynomolgus monkey were analyzed. Chemicals were deionized water, blackcurrant juice, and the four basic taste stimuli: glucose, NaCl, HCl, and quinine HCl.2. Taste-evoked responses could be recorded from an opercular region that measured -4.0 mm in its anteroposterior extent, 2.0 mm mediolaterally, and 3.0 mm dorsoventrally. Within this area, taste-responsive neurons were sparsely distributed such that mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
2
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(112 citation statements)
references
References 30 publications
8
100
2
2
Order By: Relevance
“…That is, a primary taste cortex resides in the rostral insula and adjoining frontal operculum (189)(190)(191)(192). Some studies argue that these regions provide a representation of food in the mouth that is independent of hunger, and thus is of reward value (193).…”
Section: Feeding Behaviormentioning
confidence: 99%
“…That is, a primary taste cortex resides in the rostral insula and adjoining frontal operculum (189)(190)(191)(192). Some studies argue that these regions provide a representation of food in the mouth that is independent of hunger, and thus is of reward value (193).…”
Section: Feeding Behaviormentioning
confidence: 99%
“…The primary taste cortex Rolls et al [2][3][4] have shown that the primary taste cortex in the primate anterior insula and adjoining frontal operculum contains not only taste neurons tuned to sweet, salt, bitter, sour, and umami as exemplified by monosodium glutamate (MSG), 5,6 but also other neurons that encode oral somatosensory stimuli including viscosity, fat texture, temperature and capsaicin. 7 Some neurons in the primary taste cortex respond to particular combinations of taste and oral texture stimuli, but do not respond to olfactory stimuli or visual stimuli such as the sight of food.…”
Section: Introductionmentioning
confidence: 99%
“…Brain imaging studies performed in the past decade in human and nonhuman primates show that a primary taste cortex resides in the rostral insula and adjoining frontal operculum (Scott et al, 1986;Yaxley et al, 1990;Faurion et al, 1999;Schoenfeld et al, 2004). Some studies argue that these regions provide a representation of food in the mouth that is independent of hunger, and thus of reward value (Rolls, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This concentration is present in soft drinks and is a level of sweetness preferred by the general public (Drewnowski et al, 1987;Sunday and Halmi, 1990). In primates and healthy humans, both sugar (Rolls, 2005) and water (Scott et al, 1986;Yaxley et al, 1990;Zald and Pardo, 2000;De Araujo et al, 2003a) ingestion activates neurons in the primary and secondary cortical taste areas. We hypothesize that AN women might have a disturbance of these higher order pathways modulating the sensory and hedonic aspects of feeding.…”
Section: Introductionmentioning
confidence: 99%